Desenvolvimento e validação de métodos cromatográficos para avaliação de teor/potência de insulina glargina - Schramm, Vanessa Grigoletto (2016)
hans, and is secreted into the bloodstream. It plays and important role in regulating the metabolic activities of the body, particularly the homeostasis of the blood glucose. Insulin glargine is a recombinant human insulin analogue produced by DNA technology using a strain of Escherichia coli and the insulin glargine differ only by three amino acids from human insulin. Reversed-phase liquid chromatography (RP-LC) and size exclusion liquid chromatography (SE-LC) methods were developed and validated for the assessment of insulin glargine in biopharmaceutical formulations. A RP-LC method was carried out on a Jupiter C4 column (250 mm x 4.6 mm i.d.), maintained at 30 ºC. The mobile phase A consisted of 0.05 M sodium sulphate buffer, pH 2.5, and the mobile phase B was acetonitrile. The SE-LC method was carried out on a BioSep-SEC-S 2000 column (300 mm x 7.8 mm i.d.), maintained at 25 ºC. The mobile phase consisted of 0.03 M MES acid buffer, pH 2.5, run isocratically at a flow rate of 0.6 mL/min. Chromatographic separation was obtained with retention times of 7.5 min, and 9.9 min, and was linear over the concentration range of 0.05 - 200 μg/mL (R2 = 0.9998) and 0.02 - 180 μg/mL (R2 = 0.9999), respectively, for RP-LC and SE-LC, with photodiode array (PDA) detection at 214 nm and 200 nm for RP-LC and SE-LC methods, respectively. The limits of detection and quantitation were 0.018 and 0.054 μg/mL, respectively, for the RP-LC and 0.009 and 0.027 μg/mL, for the SE-LC. Specificity was established in degradation studies, which also showed that there was no interference of the excipients. Equally, the accuracy was 100.13% and 99.38%, with bias lower than 0.85% and than 0.86%. The validated methods were applied for the determination of insulin glargine and related proteins and high molecular mass, in biotechnology-derived products, giving lower mean differences of the estimated content/potencies of 0.21% and 0.16% for the RP-LC and SE-LC related, compared to the in vitro cell culture assay. It is concluded that represents a contribution to establish alternatives to monitor stability, quality control and thereby assure therapeutic efficacy of the biotechnology-derived medicine.